Wood properties of 32-year-old Peltophorum dubium wood from two seed provenances planted in Luiz Antônio - SP, Brazil - Galão, Ana Tereza Durão; Freitas, Miguel Luiz Menezes; de Andrade Barbosa, Juraci; Tomazello-Filho, Mario; Marcati, Carmen Regina [UNESP]; de Lima, Israel Luiz; Ballarin, Adriano Wagner [UNESP]; Longui, Eduardo Luiz (Instituto de Pesquisa e Estudos Florestais (IPEF), 2023)
We studied Peltophorum dubium (Spreng.) Taub. (Fabaceae) wood, popularly known in Brazil as canafístula, from two different provenances planted in Luiz Antônio – SP, Brazil. The study aimed to characterize variations between and within provenances in the radial direction in the trunk of Peltophorum dubium trees based on average annual increment, anatomical analyses, as well as physical-mechanical properties of the wood. Thirty randomly selected trees, 15 from each provenance were collected at 32 years of age for analysis of wood properties. The provenances differed only in ray density. The wood of P. dubium varied radially and, in general, followed the typical anatomical pattern of variation, having longer and wider vessel elements with lower cell density, along with longer fibers with thicker walls close to the bark. Alvorada do Sul - PR (AS) and Bauru - SP (BA) provenances presented the highest values for most of the properties in the region close to the bark; however, these values were not always significantly different from the other positions. P. dubium wood falls into resistance class C20, the lowest among the resistance classes in angiosperms, as defined by NBR 7190 ABNT. We conclude that P. dubium is highly adaptable to many locations and that consistency in the quality of its wood can be kept between provenances.
Propriedades da madeira de Peltophorum dubium aos 32 anos de idade, oriunda de duas procedências de sementes plantadas em Luiz Antônio - SP, Brasil
Keywords: Canafístula; Pith-bark variation; Wood anatomy; Wood density; Wood strength